Root exudates contribute to belowground ecosystem hotspots: A review - Ma, Wenming; Tang, Sihong; Dengzeng, Zhuoma; Zhang, Dong; Zhang, Ting; Ma, Xiangli (Frontiers in Microbiology, 2022)
Root exudates are an essential carrier for material cycling, energy exchange, and information transfer between the belowground parts of plants and the soil. We synthesize current properties and regulators of root exudates and their role in the belowground ecosystem as substances cycle and signal regulation. We discussed the composition and amount of root exudates and their production mechanism, indicating that plant species, growth stage, environmental factors, and microorganisms are primary influence factors . The specific mechanisms by which root secretions mobilize the soil nutrients were summarized. First, plants improve the nutrient status of the soil by releasing organic acids for acidification and chelation. Then, root exudates accelerated the SOC turnover due to their dual impacts, forming and destabilizing aggregates and MASOC. Eventually, root exudates mediate the plant-plant interaction and plant-microbe interaction. Additionally, a summary of the current collection methods of root exudates is presented.